2014
DOI: 10.1002/jor.22623
|View full text |Cite
|
Sign up to set email alerts
|

HIF‐1α‐induced HSP70 regulates anabolic responses in articular chondrocytes under hypoxic conditions

Abstract: ABSTRACT:We assessed whether heat shock protein 70 (HSP70) is involved in hypoxia inducible factor 1 alpha (HIF-1a)-dependent anabolic pathways in articular chondrocytes under hypoxic conditions. Primary rabbit chondrocytes were cultured under normoxia (20% oxygen condition) or hypoxia (1% oxygen condition). Alternatively, cells cultured under normoxia were treated with CoCl 2 , which induces HIF-1a, to simulate hypoxia, or transfected with siRNAs targeting HIF-1a (si-HIF-1a) and HSP70 (si-HSP70) under hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…2, p ≤ 0.001) with a percentage change of 83.1 %. This finding was in agreement with the recent study of Tsuchida et al (23), who suggested that under hypoxia the HIF-1a-induced HSP70 overexpression in chondrocytes enhanced the metabolic activity of chondrocytes and chondroprotective effects.…”
Section: Discussionsupporting
confidence: 93%
“…2, p ≤ 0.001) with a percentage change of 83.1 %. This finding was in agreement with the recent study of Tsuchida et al (23), who suggested that under hypoxia the HIF-1a-induced HSP70 overexpression in chondrocytes enhanced the metabolic activity of chondrocytes and chondroprotective effects.…”
Section: Discussionsupporting
confidence: 93%
“…), agreeably demonstrated cell proliferation increasing considerably in a hypoxic environment. Previously, it was reported that hypoxia contributed to a better cell viability for chondrocytes cultured in hypoxic environment . We used an oxygen tension of 5% because it is well documented that 5% O 2 tension mimics physiological O 2 tension .…”
Section: Discussionmentioning
confidence: 99%
“…Catabolic-stresses, IL-1␤, and oxidative stress induce the expression of HIF-1␣ in chondrocytes. Elevated HIF-1␣ could induce heat shock protein 70 (HSP70) overexpression and increase the levels of ECM genes and cell viability, and protect chondrocytes from apoptosis [38]. Meanwhile, HIF-1␣-deficient chondrocytes show an acceleration of catabolic stress-induced apoptosis in vitro [36].…”
Section: Hif-1␣ In Cartilage and Oamentioning
confidence: 99%